Dubrovnik in the Corpus of Eastern Adriatic Humanist Laudationes Urbium - Jovanović, Neven, filolog (2012)
A digital text collection Laudationes urbium Dalmaticarum gathers and makes freely accessible and searchable 69 Latin texts by 53 authors that praised the cities of the Eastern Adriatic coast in the period 1268-1608. 'Praise of cities' is any description or mention of an Eastern Adriatic city or region, in a literary text written in Latin, that can be interpreted as a compliment (or its antithesis, a criticism). The following cities and regions are praised (listed in geographical order, from North to South): Trieste, Istria, Kopar, Dalmatia, Zadar, Šibenik, Trogir, Split, Brač, Hvar, Korčula, Ston, Dubrovnik, Kotor, and Shkodër. Most often praised is the city of Dubrovnik, with 32 texts in its honour. Next comes Split (10 texts). Dalmatia as a region is praised in seven texts, Istria in three. We examine the authors' relationship to the cities praised and the genres of the texts, with a short discussion of the three criticisms (all directed to Dubrovnik). Finally, we show (on the example of Dalmatia, Istria, Dubrovnik, Hvar, and Split) how a simple collocation analysis reveals the key terms pointing to universally accepted ideas about the identities of the places of the Eastern Adriatic.
Projekt MZOS
ENG